In vivo efficacy of a biotherapic and eugenol formulation against Rhipicephalus microplus - Valente, Paula Pimentel [UNESP]; Moreira, Gustavo Henrique Ferreira Abreu; Serafini, Matheus Ferreira; Facury-Filho, Elias Jorge; Carvalho, Antônio Último; Faraco, André Augusto Gomes; Castilho, Rachel Oliveira; Ribeiro, Múcio Flávio Barbosa (Springer Nature, 2017)
The control of Rhipicephalus microplus is essential to prevent cattle discomfort and economic losses. However, increased resistance and acaricides inefficiency lead producers to adopt strategies that could result in the accumulation of chemical residues in meat and milk with possibilities of poisoning in animals and people. This scenario demonstrates the necessity of research into the identification of novel, effective and environmentally safe therapeutic options for cattle tick control. The objectives of this study were to develop and assess the efficacy of R. microplus biotherapic and of 5% eugenol for the control of R. microplus in artificially infested calves. Eighteen male 6-month-old Holstein calves were divided into three groups of six animals. In Group 1, the animals did not receive medication (control group); in Group 2, the animals received 1 mL of R. microplus biotherapic at dilution 6CH (centesimal Hahnemannian), orally administered twice daily. And in Group 3, they received a single application of eugenol 5% in the pour-on formulation. The median efficacy for biotherapy and eugenol 5% was respectively 10.13 and 13.97%; however, upon analyzing reproductive efficiency, it is noteworthy that the biotherapic had 45.86% efficiency and was superior to the action of eugenol (12.03%) after 37 days of treatment. The ultrastructural study provided information about the effects of R. microplus biotherapic on the ovaries of engorged females and showed disorganization in the deposition of the oocyte exochorion. The results suggest hatchability inhibition of larvae, interference in R. microplus reproduction and future possibilities for eco-friendly control of R. microplus with biotherapic 6CH.
Keywords: Cattle tick; Eco-friendly control; Homeopathy; Pour on; Ultrastructure